Laundry Service/ Michael Thaddeus Simon Siket… [et.al] - Simon Siket, Michael Thaddeus; Hamdan, Mohammad Noor Azuan; Abdul Manan, Razali; Anyi, Victor (2010)
Administration is an important part in an organization or heart of the organization. It is a process of managing an administration task in a business. A successful business is the aim of every entrepreneur. In order to strike for that goal, we have to start from the roots, which is administration. The implementation of an efficient and systematic management will lead to a successful business.